AN ANALYSIS OF CONTEXTUAL MEANING ON THE IDIOMATIC EXPRESSION IN THE PARENT TRAP FILM SCRIPT - Choerunnisa, Putri Destyanti (2013)
Idiomatic expressions are often used by the people when they are communicating. Idiom is an expression which can be a term or a group of words whose meaning cannot be deduced from the literal definitions. The Meaning of idiomatic expression can be defined by contextual meaning, whereas contextual meaning is the meaning of a word according to the situations in which they are used. In clarifying the meaning of idiom, it is not only finding the word from the dictionary, but also understanding with the speaker's condition when uttering the message. So, contextual theory is used in analyzing the idiomatic meaning. This study analyzed the contextual meaning on the idiomatic expressions found in The Parent Trap's film script as an object of the study. The researcher attempted to answer the two research questions, they are: 1) What types of idioms are found in The Parent Trap Film script? and 2) What contextual meanings of the idioms are found in The Parent Trap film script? In conducting the research, the researcher applied descriptive qualitative method to analyze all the selected samples in order to classify and interpret them. The researcher found 97 out of six types of idioms. There were 44 out 97 idioms where the meaning was based on the context, and there were 53 idioms which had the same meaning with the meaning in the dictionary of idioms. It is indicated that the contextual meaning of idioms could have in common with the meaning of words contained in the dictionary or the real meaning of its idioms. It is also proved that a meaning is having a close relationship with its context because in this case, in understanding the meaning of idioms, in addition to see the original meaning, it also need to see the context when the idioms is uttered/spoken. The researcher hopes that there will be more students of English Department who are interested in analyzing idiomatic expressions in the film to increase their knowledge such as literature, linguistics, and translation study. Keywords: idiomatic expressions, contextual meaning, film